This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
dude you don't need to use logarithm,
Log in to reply
Taking logarithm on both sides to bring the powers down is a more logical way than just comparing L.H.S and R.H.S. That's the reason why he used logarithm!
9 2 x × 9 − 4 = 2 7 x 3 4 x × 3 − 8 = 3 3 x 3 4 x − 8 = 3 3 x Equating 4 x − 8 = 3 x ⟹ x = 8
(This solution uses logarithm because the topic says so) 9 2 x − 4 lo g 3 9 2 x − 4 ( 2 x − 4 ) lo g 3 9 2 ( 2 x − 4 ) 4 x − 8 x − 8 x = = = = = = = 2 7 x lo g 3 2 7 x x lo g 3 2 7 3 x 3 x 0 8
It took me a while to figure out what the question was lol ;)
3^(4x - 8) = 3^3x 4x - 8 = 3x x = 8
Just use the rules of logs.
Equating, you get 4x - 8 = 3x
thus,
x = 8
\( { 27 }^{ x }\quad =\quad { 9 }^{ x }\quad \times \quad { 3 }^{ x }\quad =\quad { 9 }^{ x }\quad \times \quad { 9 }^{ 1/2\quad x }\quad =\quad { 9 }^{ 3/2\quad x }\ \gg \quad 2x\quad -\quad 4\quad =\quad 3/2\quad x\quad \ \gg \quad x\quad =\quad 8 \)
Problem Loading...
Note Loading...
Set Loading...
9 2 x − 4 = 2 7 x can be written as 3 2 ( 2 x − 4 ) = 3 3 x now taking log both sides with base 3 lo g 3 3 2 ( 2 x − 4 ) = lo g 3 3 3 x which simply gives 4 x − 8 = 3 x hence x = 8